KAJIAN EPIDEMI PENYAKIT KANKER BATANG DUKU DI PROVINSI JAMBI - , SIGID HANDOKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Duku (Lansium domesticum Corr.) was one of the important plant commodities in Jambi Province, which it has significant contribution to the regional revenue. However, during 2004 to 2011, the production of duku was significantly decreased around 93.73%, which was caused especially by stem canker. Stem canker has been spreading since 2003 in six regencies in the Jambi Province. The increment of disease intensity from 2004 until 2011 was recorded as 40.53% from a population of 365,729 duku trees. The observation conducted in 2012 showed that the highest intensity of disease was occured in Batanghari regency (61.33%), and the lowest was in Muaro Jambi regency (21.33%). The disease formed clustered distribution